ANALISIS PENGARUH PERTUMBUHAN EKONOMI, INVESTASI DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP KETIMPANGAN PENDAPATAN DI KABUPATEN/KOTA PROVINSI SUMATERA UTARA - Siti Holijah Harahap (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to determine how much influence the Economic Growth, Investm ent and Human Development Index, both partially and simultaneously on income inequality between districts / cities in North Sumatra Province. The data used in this study are secondary data with panel data types, combined time series and cross sections from 2014-2018 and 33 Regencies / Cities of North Sumatra Province. The variables used are Inequality Income (Y), Economic Growth (X1), Investment (X2) and Human Development Index (X3). In analyzing the data used multiple linear regression models using Eviews.The results of this study indicate that economic growth, investment and HDI simultaneously affect income inequality. While partially only HDI has a positive and significant effect on income inequality. The panel data regression model used is the Random Effect Model (REM).